Low-pH-induced fusion of Vero cells infected with Junin virus - Castilla, V. (Arch Virol, 1996)
Junin virus (JV) infected Vero cells were used to investigate virus capacity to induce cell-cell fusion. Polykaryocyte formation due to JV was found to be pH and temperature-dependent. A reduced fusion activity was detected on BHK-21 cells. Different JV-strains exhibited a similar extent and pH dependence of their fusion activity. Neutralizing antibodies against the main viral glycoprotein (GP38) inhibited syncytium production and GP38 conformational changes in response to acid treatment were detected by an immunoprecipitation assay.